2021
DOI: 10.1021/acs.est.1c00691
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of Air–Sea Exchange of Mercury in the Global Ocean: The “Seesaw Effect” in the Equatorial Pacific and Contributions to the Atmosphere

Abstract: Air–sea exchange of gaseous elemental mercury (Hg(0)) is influenced by different meteorological factors and the availability of Hg in seawater. Here, we use the MITgcm ocean model to explore the interannual variability of this flux and the influence of oceanographic and atmospheric dynamics. We apply the GEOS-Chem model to further simulate the potential impact of the evasion variability on the atmospheric Hg levels. We find a latitudinal pattern in Hg(0) evasion with a relatively small variability in mid-latit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 99 publications
1
10
0
Order By: Relevance
“…As shown in Fig. S3, the levels of CO, NO 2 , and PM 2.5 in the Yangtze River Delta (YRD) declined sharply during the lockdown by 26 %, 61 %, and 27 %, respectively, which was consistent with emissions estimates based on up-to-date activity levels in eastern China (Huang et al, 2021). For anthropogenic Hg emissions, one study in the Beijing-Tianjin-Hebei region estimated a decline of approximately 22 % during the lockdown, which was mainly due to the reduction in cement clinker production, coal-fired power plants, and residential coal combustion (Wu et al, 2021).…”
Section: Changes In Gem Concentrations During the Lockdownsupporting
confidence: 81%
See 1 more Smart Citation
“…As shown in Fig. S3, the levels of CO, NO 2 , and PM 2.5 in the Yangtze River Delta (YRD) declined sharply during the lockdown by 26 %, 61 %, and 27 %, respectively, which was consistent with emissions estimates based on up-to-date activity levels in eastern China (Huang et al, 2021). For anthropogenic Hg emissions, one study in the Beijing-Tianjin-Hebei region estimated a decline of approximately 22 % during the lockdown, which was mainly due to the reduction in cement clinker production, coal-fired power plants, and residential coal combustion (Wu et al, 2021).…”
Section: Changes In Gem Concentrations During the Lockdownsupporting
confidence: 81%
“…Therefore, the COVID-19 lockdown provided a natural experiment to explore how the natural surface emissions of mercury would respond to the dramatic reduction in anthropogenic mercury emissions. Traditionally, chemical transport models were the most widely used tools for disentangling the contributions from meteorology and various emission sources, while the performance of these models relied heavily on the availability of updated emission inventories with high accuracy (Selin et al, 2007;Holmes et al, 2010;Huang and Zhang, 2021). Therefore, applying traditional models to reproduce and explain some special events and processes of atmospheric mercury could be limited by certain uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptionally high ATARS Hg was near‐exclusively linked to northerly equator‐crossing air masses and not to easterlies from the SH tropical Pacific. In another line of evidence, a recent modeling study suggests that atmospheric Hg variations in South America as consequence of ENSO‐related anomalies in oceanic emissions do usually not exceed ∼5% of the multiyear mean, and that potential positive concentration anomalies recently manifest after the peak of El Niño (Huang & Zhang, 2021). They also estimated that during the 2015–2016 El Niño in particular, oceanic Hg emissions from the equatorial or SH tropical Pacific were reduced, not increased, mainly due to a reduction in surface wind speeds (Huang & Zhang, 2021 and corresponding Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Such a shift enhances convection over the central equatorial Pacific and tends to suppress convection over tropical South America, favoring the subsidence of westerly air masses from the Pacific sector (Ambrizzi et al., 2004; Grimm & Ambrizzi, 2009; Lau & Yang, 2015). ENSO can alter ocean re‐emissions (Chatterjee et al., 2017; Huang & Zhang, 2021), BB emissions (Y. Chen et al., 2011; Liu et al., 2017), and gas exchange by vegetation (Bastos et al., 2018; Koren et al., 2018; Liu et al., 2017). However, while previous studies have suggested that ENSO could impact tropospheric Hg concentrations (Franz Slemr et al., 2016), the magnitude of the CHC TGM increase during the 2015–2016 El Niño is unprecedented.…”
Section: Introductionmentioning
confidence: 99%
“…The model couples a global anthropogenic Hg emission inventory [e.g., World Hg Emission Trends (WHET)], a global biomass burning Hg emission inventory [e.g., Global Fire Emissions Database (GFED-4)], and updated mechanisms for Hg redox chemistry . The constant monthly oceanic evasion of Hg 0 is coupled in the GEOS-Chem model, which is outputted from the MITgcm model (Massachusetts Institute of Technology General Circulation Model) . The model was run from 2016 to 2018 in the standard mode (which considers the emissions of anthropogenic and biomass burning sources), and was run from 2014 to 2018 in the mode that turned off the WHET anthropogenic mercury emission inventory and GFED-4 biomass burning mercury emission inventory (with two years of running time more than the standard mode, in order to eliminate the impact of anthropogenic emissions on atmospheric Hg latitudinal gradient in model), respectively.…”
Section: Methodsmentioning
confidence: 99%